Wheat Variety Response to Intensive vs. Standard Management Strategies to Narrow the Yield Gap in Kansas - A. de Oliveira Silva; A. K. Fritz; R. Lollato (Kansas Agricultural Experiment Station Research Reports, 2017)
Farmer-reported wheat grain yield in Kansas is approximately 35 bushels per acre lower than the estimated yield potential of 75 bushels per acre. Our objective was to determine the influence of variety selection and management on grain yield to elucidate methods to decrease the wheat yield gap in Kansas. Field experiments were conducted at three locations (Ellsworth, Conway Springs and McPherson) in Kansas during the 2015-2016 growing season to evaluate variety-specific response to nitrogen (N) and foliar fungicide. At each site, 35 to 44 winter wheat varieties were evaluated under standard management practice (SM) based on current farmer’s practice of each region, versus intensive management (IM) with an additional 40 pounds of N per acre applied at Feekes growth stage 3 (GS3) and two fungicide applications (Feekes GS6 and GS10). Yield gap between the IM and SM ranged from 4 bushels per acre in McPherson to 19 bushels per acre in Ellsworth, due to a severe stripe rust (Puccinia striiformisWestend) epidemic. Varieties more susceptible to stripe rust had 50% cumulative probability yield gain of 13 bushels per acre across all locations studied in KS by switching from SM to IM, while resistant varieties gained 5 bushels per acre. The probability of breakeven was about two times greater in susceptible varieties as compared to resistant varieties. Our results indicate that selecting varieties with resistance to major fungal diseases can sustainably narrow the wheat yield gap in most years, reducing the need for additional fungicide. Notwithstanding, optimized management system is warranted for varieties that lack the aforementioned genetic resistance.
Keywords: Wheat yield gain; Foliar fungal diseases; Profitability; Yield gap